Protective effect of aqueous garlic extract against naphthalene-induced oxidative stress in mice - ŞENER, GÖKSEL (WILEY, 2005)
The aim of this study was to investigate the possible protective effects of aqueous garlic extract (AGE) against naphthalene-induced oxidative changes in liver, kidney, lung and brain of mice. Balb/c mice (25-30 g) of either sex were divided into five groups each comprising 10 animals. Mice received for 30 days: 0.9% NaCl, i.p. (control); corn oil, i.p; AGE in a dose of 125 mg kg(-1), i.p.; naphthalene in a dose of 100 mg kg(-1), i.p. (dissolved in corn oil); and AGE (in a dose of 125 mg kg(-1), i.p.) plus naphthalene (in a dose of 100 mg kg(-1), i.p.). After decapitation, liver, kidney, lung and brain tissues were excised. Malondialdehyde (MDA) and glutathione (GSH) levels and myeloperoxidase activity (MPO) were determined in the tissues, while oxidant-induced tissue fibrosis was determined by collagen content. Tissues were also examined microscopically. Serum aspartate aminotransferase, alanine aminotransferase levels and blood urea nitrogen and creatinine concentrations were measured for the evaluation of hepatic and renal function, respectively. MDA and GSH levels were also assayed in serum samples. In the naphthalene-treated group, GSH levels decreased significantly, while MDA levels, MPO activity and collagen content increased in the tissues (P < 0.01-0.001), suggesting oxidative organ damage, which was also verified histologically. In the AGE-treated naphthalene group, all of these oxidant responses were reversed significantly (P < 0.05-0.01). Hepatic and renal function test parameters, which increased significantly (P < 0.001) following naphthalene administration, decreased (P < 0.05-0.001) after AGE treatment. The results demonstrate the role of oxidative mechanisms in naphthalene-induced tissue damage. The antioxidant properties of AGE ameliorated oxidative organ injury due to naphthalene toxicity.
Keywords: VASCULAR ENDOTHELIAL-CELLS; SUPEROXIDE-DISMUTASE; INDUCED TOXICITY; TISSUE-DAMAGE; ALBINO-RATS; VITAMIN-E; GLUTATHIONE; MELATONIN; MYELOPEROXIDASE; ATTENUATION